Are Tobacco Taxes Really Regressive? : Evidence from Chile - Fuchs, Alan; Meneses, Francisco (World Bank, Washington, DC, 2017)
Tobacco taxes are deemed regressive, because the poorest families tend to allocate larger shares of their budget to purchase tobacco. However, as taxes also discourage tobacco use, some of the most adverse effects, including higher medical expenses, lower life expectancy at birth, added years of disability among smokers, and reduction in the quality of life, among others, would be reduced. This paper describes and simulates the effects of the tobacco tax on incomes in Chile assuming three different price-elasticity scenarios for different income deciles of the population. The results show that although increasing the price of tobacco through higher taxes generates negative income variations across all groups in a population, under a more comprehensive scenario that includes benefits through lower medical expenses and an increase in working years, the results invert, and the overall monetary effect of the taxation policy becomes positive. Moreover, the reduction in medical expenses seems to be the main driver of the increase in net incomes, because of the reduction in tobacco-related problems that require expensive treatments. Lastly, as the distributional effects of tobacco taxes are directly related to the long-term price elasticities of tobacco consumption, it would be advisable to coordinate taxation and behavioral change policies across income groups.